Enhancing potential fields using stable downward continuation and boundary filters: Application to the Central Highlands, Vietnam - Pham Thanh, Luan; P. Oliveira, Saulo; Duc Luu, Long; Tuan Do, Long (Vietnam Journal of Earth Sciences, 2025)
The stable downward continuation method can enhance low amplitude anomalies and improve the resolution of potential fields. However, this method may be affected by the edge effect. In this paper, we improve the downward continuation results by using the cubic Hermite interpolation to extend data. Our synthetic model shows that the proposed extension can provide better estimates, especially at the edges, than using constant values. We further enhance downward continued data using boundary filters where the boundaries obtained from the downward continued data have a higher resolution. The methods are also applied to interpret RTP magnetic and Bouguer gravity anomalies of the Central Highlands (Vietnam), where the RTP magnetic data are determined from the multiple-stage RTP method, while the Bouguer gravity data are calculated using the Parker formula. The spectral analysis of potential fields reveals the depth of shallow sources in the area of about 1 km, which determines the height of the downward continuation. A new subsurface structural map is established for the Central Highlands from the filtered results of downward continued data, which will be a helpful document for detailed future explorations and geology studies of the area.